Strategic SWOT and RSM Analysis on Performance Assessment of WC/Cu Powder Metallurgy Electrode in EDM of AISI-D2 Tool Steel - Mathiazhagan, Shalini; Arjunan, Visagan; Uthirapathi, Elaiyarasan; Bareedu, Vinod (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
The study experimentally investigates the Electrical Discharge Machining (EDM) performance of AISI-D2 tool steel using a powder metallurgy (PM) fabricated WC/Cu electrode compared to a conventional Cu electrode. EDM parameters such as discharge current (Id), pulse-on time (Pon), and pulse-off time (Poff) were optimized using response surface methodology (RSM) to evaluate material removal rate (MRR), tool wear rate (TWR), and surface roughness (Ra). The WC/Cu PM electrode demonstrated a 33% improvement in MRR, 40.8% reduction in TWR, and 12% improvement in Ra compared to the Cu electrode. SEM analysis revealed enhanced surface integrity, including fine craters, thinner recast layers and fewer microcracks, attributed to the enhanced thermal stability and spark energy concentration of the PM electrode. Furthermore, SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis highlighted the strategic strengths of WC/Cu PM electrode, emphasizing increased machining efficiency, extended electrode life, and alignment with sustainable manufacturing practices, underscoring their industrial applicability.